Tyrosine kinase inhibitors in patients with advanced anaplastic thyroid cancer: an effective analysis based on real-world retrospective studies - Kuang, Bo-Hua; Zhang, Wen-Xuan; Lin, Guo-He; Fu, Chen; Cao, Ru-Bo; Wang, Bi-Cheng (Frontiers in Endocrinology, 2024)
Background: Tyrosine kinase inhibitors (TKIs) contribute to the treatment of patients with anaplastic thyroid cancer (ATC). Although prospective clinical studies of TKIs exhibit limited efficacy, whether ATC patients benefit from TKI treatment in real-world clinical practice may enlighten future explorations. Therefore, we conducted this effective analysis based on real-world retrospective studies to illustrate the efficacy of TKI treatment in ATC patients.We systematically searched the online databases on September 03, 2023.Survival curves were collected and reconstructed to summarize the pooled curves.Responses were analyzed by using the "meta" package. The primary endpoints were progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and disease control rate (DCR).Results: 12 studies involving 227 patients were enrolled in the study. Therapeutic strategies included: anlotinib, lenvatinib, dabrafenib plus trametinib, vemurafenib, pembrolizumab plus dabrafenib and trametinib, pembrolizumab plus lenvatinib, pembrolizumab plus trametinib, and sorafenib. The pooled median OS and PFS were 6.37 months (95% CI 4.19-10.33) and 5.50 months (95% CI 2.17-12.03). The integrated ORR and DCR were 32% (95% CI 23%-41%) and 40% (95% CI 12%-74%).In real-world clinical practice, ATC patients could benefit from TKI therapy. In future studies, more basic experiments and clinical explorations are needed to enhance the effects of TKIs in the treatment of patients with ATC.